Comparison of scores of bilingual urban and monolingual suburban elementary school children for two measures of intelligence - Murphy, D.G. (Psychological Reports, 1990)
Keywords: article; child; dept.csp; human; intelligence; language; mental test; normal human

Preliminary study of effect of decision making on locus of control among prison inmates - Murphy, D.G. (Psychological Reports, 1990)
To study the effect of teaching decision-making to inmates in a maximum security facility on locus of control 19 adult male inmates who were incarcerated at a community correctional center were pre- and posttested on the Rotter Internal-External Locus of Control Scale. In this preliminary study there was no statistically significant difference at pretest or posttest so teaching decision-making skills in group settings versus teaching in a group combined and one-to-one contact did not affect locus of control as measured. This personality trait appears stable over time and a more thorough means of intervention is required to effect change.
Keywords: adult; article; clinical article; decision making; dept.csp; human; male; personality; prisoner

Gifted: the end of a tail. - Falk, Carolyn R (Gifted Education International, 1990)
Special education in the United States services a diverse population, including those students whose academic performance falls at the ends of the normal distribution. This article challenges the assumption that a continuum of learning opportunities appropriate for exceptional persons is possible when the concept of the normal distribution is used. An alternate model, a bull's-eye, is suggested to accommodate the openended potential for the gifted population. © 1990 A B Academic Publishers Printed in Great Britain.
Keywords: dept.csp